Do Tax Incentives Affect Business Location and Economic Development? Evidence from State Film Incentives - Patrick Button (Institute of Labor Economics (IZA), 2019)
I estimate the impacts of recently-popular U.S. state film incentives on filming location, film industry employment, wages, and establishments, and spillover impacts on related industries. I compile a detailed database of incentives, matching this with TV series and feature film data from the Internet Movie Database (IMDb) and Studio System, and establishment and employment data from the Quarterly Census of Employment and Wages and Country Business Patterns. I compare these outcomes in states before and after they adopt incentives, relative to similar states that did not adopt incentives over the same time period (a panel difference-in-differences). I find that TV series filming increases by 6.3 to 55.4% (0.67 to 1.50 additional TV series) after incentive adoption. However, there is no meaningful effect on feature films, and employment, wages, and establishments in the film industry and in related industries. These results show that the ability for tax incentives to affect business location decisions and economic development is mixed, suggesting that even with aggressive incentives, and "footloose" filming, incentives can have little impact.
Keywords: H25; H71; R38; L82; Z11; 330; economic development; tax incentives; state taxation; business location; film industry